Spinal Cavernomas: Outcome of Surgically Treated 10 Patients - Ibrahim Sun; M. Necmettin Pamir (Frontiers in Neurology, 2017)
AimWe report the preoperative and postoperative findings and also neurological follow-up results from 10 spinal cavernoma patients treated in our clinic. Several representative cases are presented in terms of clinical features, imaging results, and surgical outcomes.Material and methodsThe data were retrospectively collected from patients’ files in the hospital records and sorted with regards to clinical presentation, radiologic features, and operative findings. Patients received spinal MRI scans for the diagnosis of spinal cavernomas (SC) and postsurgical evaluation. Clinical presentation was evaluated via Ogilvy classification and symptoms were checked preoperatively and postoperatively at third month and first year using McCormick scale. Primary treatment was microsurgical operation aiming a gross total lesion resection.Results10 spinal cavernoma patients between the ages 30 and 63 were treated. Six (60%) of the patients were diagnosed with cervical and four (40%) others were diagnosed with thoracic SC. Among the patient group, mean preoperative Ogilvy classification score was 2.3 ± 0.7.8 and McCormick score was 1.9 ± 0.7. There was no residual mass or relapse after surgery. One patient developed surgery-related left hemiparesis, which was normalized at 1 year follow-up.ConclusionPatients must be diagnosed with MRI since it is nowadays a gold standard. Preoperative and postoperative scores are important in evaluating the patients’ condition and improvement. The results from our patient series also reinforce the notion that immediate surgery should be the preferred treatment method for cavernomas. Intraoperative neurophysiologic monitarization should assist the surgery in order to prevent complications. In conclusion, microsurgery is a gold standard method that we recommend for cases of cavernomas, which will not recur if gross total resection is achieved.